A study of parents' child raising styles and marital harmony - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This research is conducted to investigate the relation between parents' child raising styles and their marital harmony with children at age 5-6 and attending preschool in Istanbul. The upbringing styles are investigated in three categories; authoritative, authoritarian and permissive. The significant results indicate that there is a positive relation between authoritative upbringing and marital harmony; a negative relation between authoritarian and permissive upbringing and marital harmony. According to these findings we may conclude that as the parent's authoritative style scores increase the marital harmony scores also increases; at the other hand, as the authoritarian and permissive scores on the child raising styles increase their marital harmony scores decreases. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Parenting styles; child rearing styles; marital harmony; 5-6 years-old preschool children